Management of chronic recurrent osteitis pubis/pubic bone stress in a Premier League footballer: Evaluating the evidence base and application of a nine-point management strategy. Issue 3 (August 2015) - McAleer, Stephen S.; Gille, Justus; Bark, Stefan; Riepenhof, Helge
Abstract Background/Aim The aim of this paper was to use a clinical example to describe a treatment strategy for the management of recurrent chronic groin pain and evaluate the evidence of the interventions. Methods A professional footballer presented with chronic recurrent OP/PBS. The injury was managed successfully with a nine-point programme – 1. Acute pharmacological management. 2. Tone reduction of over-active structures. 3. Improved ROM at hips, pelvis and thorax. 4. Adductor strength. 5. Functional movement assessment. 6. Core stability. 7. Lumbo-pelvic control. 8. Gym-based strengthening. 9. Field-based conditioning/rehabilitation. The evidence for these interventions is reviewed. Results The player returned to full training and match play within 41 and 50 days, respectively, and experienced no recurrence of his symptoms in follow up at 13 months. Conclusion This case report displays a nine-point conservative management strategy for OP/PBS, with non-time dependent clinical objective markers as the progression criteria in a Premier League football player.